1980
DOI: 10.1042/bj1920579
|View full text |Cite
|
Sign up to set email alerts
|

Reduced lysyl oxidase activity in skin fibroblasts from patients with Menkes' syndrome

Abstract: Lysyl oxidase activity against both collagen and elastin substrates has been examined in the culture medium of skin fibroblasts derived from unrelated patients with Menkes' syndrome and from control subjects. The medium of three Menkes' fibroblast lines showed 3--30% of the activity present in the medium of control fibroblasts, against a purified collagen substrate. Lysyl oxidase activity in the culture medium of two of the Menkes' fibroblast lines was also examined by using a crude aortic-elastin substrate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(72 citation statements)
references
References 29 publications
3
68
1
Order By: Relevance
“…The ability of the Menkes protein to deliver copper to Fet3p is common to Ccc2p (16) and the Wilson disease protein (11). These findings are consistent with the original observations in Menkes patient fibroblasts of elevated intracellular copper (27,28), concomitant with reduced activity of the secreted copper-dependent enzyme lysyl oxidase (29). The data are also consistent with recent studies on the localization of the yeast Menkes homologue Ccc2p to a late or post-Golgi compartment (30) as well as immunocytochemical studies that have localized the human and rodent Menkes protein to the trans-Golgi network (8 -10) where this ATPase would be positioned to transport copper for incorporation into nascent cupro enzymes within the secretory pathway.…”
Section: Discussionsupporting
confidence: 81%
“…The ability of the Menkes protein to deliver copper to Fet3p is common to Ccc2p (16) and the Wilson disease protein (11). These findings are consistent with the original observations in Menkes patient fibroblasts of elevated intracellular copper (27,28), concomitant with reduced activity of the secreted copper-dependent enzyme lysyl oxidase (29). The data are also consistent with recent studies on the localization of the yeast Menkes homologue Ccc2p to a late or post-Golgi compartment (30) as well as immunocytochemical studies that have localized the human and rodent Menkes protein to the trans-Golgi network (8 -10) where this ATPase would be positioned to transport copper for incorporation into nascent cupro enzymes within the secretory pathway.…”
Section: Discussionsupporting
confidence: 81%
“…[9][10][11][12][13][14][15] Because during the whole intrauterine life, the circulating copper is provided by the mother, early vascular wall impairment points to a key role of ATP7A for lysyl oxidase function within the cell. 16 The absence of intracranial artery ectasia and stenosis, either at onset or at follow-up, is another important result. Previous studies have reported possible ectasia or distal narrowing of intracranial arteries.…”
Section: Intracranial Vascular Changesmentioning
confidence: 99%
“…Failure to transport copper to the fetus during development results in reduced activity of Cu-dependent enzymes, leading to severe mental retardation; connective tissue abnormalities; steely, white, brittle hair; and ultimately death by the age of three years. Wilson disease is an autosomally inherited, Cu toxicosis disorder resulting from defective biliary excretion of Cu, resulting in Cu accumulation primarily in liver but also in the brain, kidney, cornea, and spleen (Royce et al, 1980;Bingham et al, 1998). In addition, serum plasma Cu concentrations are reduced because of a failure to incorporate Cu into the apo-form of ceruloplasmin before its release into serum.…”
Section: Leazer and Klaassenmentioning
confidence: 99%